38=-4(g+3)+7(-2-4g)

Simple and best practice solution for 38=-4(g+3)+7(-2-4g) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 38=-4(g+3)+7(-2-4g) equation:


38=-4(g+3)+7(-2-4g)

We simplify the equation to the form, which is simple to understand
38=-4(g+3)+7(-2-4g)

Reorder the terms in parentheses
38=+(-4g-12)+7*(-2-4g)

Remove unnecessary parentheses
+38=-4g-12+7+*(-2-4g+)

Reorder the terms in parentheses
38=-4g-12+(-14-28g)

Remove unnecessary parentheses
+38=-4g-12-14-28g

We move all terms containing g to the left and all other terms to the right.
+4g+28g=-12-14-38

We simplify left and right side of the equation.
+32g=-64

We divide both sides of the equation by 32 to get g.
g=-2

See similar equations:

| 6(2x-3)+2(6x+2)=2(x+1) | | 3y+3(1-y)-y=10 | | (2x-5)+15=67 | | 6(y-5)=4(4+y) | | -2x^2+5x+33=21 | | b+21/6=-13/8 | | -2x^2+5x+33=0 | | 6(4-5)=4(4+y) | | -5(2b+7)-7(-b-8)=0 | | 4x+5y=19 | | 2x^2-5x-33=21 | | 3y^2+7=2y | | 6y-30=16+4y | | -48=6(-6h-2) | | 4(2x-5)15=67 | | 7ln(2x+5)=8 | | 4x+5x=19 | | -8+6p=4(7+6p) | | k/100=0.15 | | 9+9n=-162 | | -(7b+7)=-14 | | k/20=0.15 | | k/8=6 | | 8x+12=11X | | g/2=16 | | -22-7n=-6+3(1-2n) | | -6y+9+4y=13 | | 8f=24 | | -3(1x+4)=-4x | | 4a^2+9a+1=0 | | x^2+3x+2=7 | | 5=-7y |

Equations solver categories